Bifunctional thiourea-catalyzed asymmetric [3 + 2] annulation reactions of 2-isothiocyanato-1-indanones with barbiturate-based olefins - Zhai, Jiang-Song; Du, Da-Ming (Beilstein Journal of Organic Chemistry, 2022)
Bifunctional thiourea-catalyzed asymmetric [3 + 2] annulation reactions of 2-isothiocyanato-1-indanones with barbiturate-based olefins have been developed to afford chiral dispiro[indene-pyrrolidine-pyrimidine]s. Through this strategy, the target products could be obtained in good to excellent yields with excellent stereoselectivities. In addition, the synthetic utility was verified through a gram-scale synthesis, one-pot three-component reactions and further transformation experiments of the products.
Keywords: asymmetric catalysis; cyclization reaction; Michael addition; one-pot three-component reaction; spirobarbiturates

(untitled) - Svendsen, O.; Arnt, J.; Boeck, V.; Bøgesø, K. P.; Christensen, A. V.; Hyttel, J.; Larsen, J.-J. (Drug Dev. Res., 1986)

(untitled) - Bianco, G. G.; Ferraz, H. M. C.; Costa, A. M.; Costa-Lotufo, L. V.; Pessoa, C.; de Moraes, M. O.; Schrems, M. G.; Pfaltz, A.; Silva, L. F., Jr (J. Org. Chem., 2009)

(untitled) - Miyauchi, Y.; Jesmin, S.; Sakai, S.; Kamiyama, J.; Shimojo, N.; Rahman, A.; Islam, M.; Zaedi, S.; Maeda, S.; Maruyama, H.; Mizutani, T.; Homma, S.; et al. (Life Sci., 2014)

(untitled) - Borie, C.; Ackermann, L.; Nechab, M. (Chem. Soc. Rev., 2016)

(untitled) - Decker, A. M.; Blough, B. E. (J. Pharmacol. Toxicol. Methods, 2018)

(untitled) - Mizuta, S.; Tsuzuki, T.; Fujimoto, T.; Yamamoto, I. (Org. Lett., 2005)

(untitled) - Gabriele, B.; Mancuso, R.; Veltri, L. (Chem. – Eur. J., 2016)

(untitled) - Feng, Z.; Yuan, Z.; Zhao, X.; Huang, Y.; Yao, H. (Org. Chem. Front., 2019)

(untitled) - Prasher, P.; Sharma, M. (ChemistrySelect, 2021)

(untitled) - Laina‐Martín, V.; Fernández‐Salas, J. A.; Alemán, J. (Chem. – Eur. J., 2021)

(untitled) - Hu, J.; Hirao, H.; Li, Y.; Zhou, J. S. (Angew. Chem., Int. Ed., 2013)

(untitled) - Yue, G.; Lei, K.; Hirao, H.; Zhou, J. S. (Angew. Chem., Int. Ed., 2015)

(untitled) - Matsuda, T.; Watanuki, S. (Org. Biomol. Chem., 2015)

(untitled) - Léonard, N. G.; Palmer, W. N.; Friedfeld, M. R.; Bezdek, M. J.; Chirik, P. J. (ACS Catal., 2019)

(untitled) - Zhao, B.-L.; Du, D.-M. (Org. Lett., 2018)

(untitled) - Hou, X.-Q.; Lin, Y.; Du, D.-M. (Org. Chem. Front., 2021)

(untitled) - Hou, X.-Q.; Wen, J.-B.; Yan, L.; Du, D.-M. (Org. Biomol. Chem., 2021)

(untitled) - Kim, S.-H.; Pudzianowski, A. T.; Leavitt, K. J.; Barbosa, J.; McDonnell, P. A.; Metzler, W. J.; Rankin, B. M.; Liu, R.; Vaccaro, W.; Pitts, W. (Bioorg. Med. Chem. Lett., 2005)

(untitled) - Duan, J. J.-W.; Chen, L.; Lu, Z.; Jiang, B.; Asakawa, N.; Sheppeck, J. E., II; Liu, R.-Q.; Covington, M. B.; Pitts, W.; Kim, S.-H.; Decicco, C. P. (Bioorg. Med. Chem. Lett., 2007)

(untitled) - Bhaskarachar, R. K.; Revanasiddappa, V. G.; Hegde, S.; Balakrishna, J. P.; Reddy, S. Y. (Med. Chem. Res., 2015)

(untitled) - Xu, H.; Huang, R.-L.; Shu, Z.; Hong, R.; Zhang, Z. (Org. Biomol. Chem., 2021)

(untitled) - Galati, E. M.; Monforte, M. T.; Miceli, N.; Raneri, E. (Farmaco, 2001)

(untitled) - Ingle, V. N.; Gaidhane, P. K.; Dutta, S. S.; Naha, P. P.; Sengupta, M. S. (J. Carbohydr. Chem., 2006)

(untitled) - Renard, A.; Lhomme, J.; Kotera, M. (J. Org. Chem., 2002)

(untitled) - Lomlim, L.; Einsiedel, J.; Heinemann, F. W.; Meyer, K.; Gmeiner, P. (J. Org. Chem., 2008)

(untitled) - Ramachary, D. B.; Reddy, Y. V.; Banerjee, A.; Banerjee, S. (Org. Biomol. Chem., 2011)

(untitled) - Hosseini, Y.; Rastgar, S.; Heren, Z.; Büyükgüngörc, O.; Pesyan, N. N. (J. Chin. Chem. Soc., 2011)

(untitled) - Huang, Z.; Zhao, Q.; Chen, G.; Wang, H.; Lin, W.; Xu, L.; Liu, H.; Wang, J.; Shi, D.; Wang, Y. (Molecules, 2012)

(untitled) - Liu, H.; Liu, Y.; Yuan, C.; Wang, G.-P.; Zhu, S.-F.; Wu, Y.; Wang, B.; Sun, Z.; Xiao, Y.; Zhou, Q.-L.; Guo, H. (Org. Lett., 2016)

(untitled) - Zhao, H.-W.; Tian, T.; Li, B.; Yang, Z.; Pang, H.-L.; Meng, W.; Song, X.-Q.; Chen, X.-Q. (J. Org. Chem., 2015)

(untitled) - Zhao, H.-W.; Tian, T.; Pang, H.-L.; Li, B.; Chen, X.-Q.; Yang, Z.; Meng, W.; Song, X.-Q.; Zhao, Y.-D.; Liu, Y.-Y. (Adv. Synth. Catal., 2016)

(untitled) - An, T.-L.; Du, D.-M. (ChemistrySelect, 2019)

(untitled) - Liu, Y.; Yang, W.; Wu, Y.; Mao, B.; Gao, X.; Liu, H.; Sun, Z.; Xiao, Y.; Guo, H. (Adv. Synth. Catal., 2016)

(untitled) - Zhu, Y.; Malerich, J. P.; Rawal, V. H. (Angew. Chem., Int. Ed., 2010)

(untitled) - Yang, W.; Du, D.-M. (Org. Lett., 2010)

(untitled) - Yang, W.; Du, D.-M. (Adv. Synth. Catal., 2011)

(untitled) - Vakulya, B.; Varga, S.; Csámpai, A.; Soós, T. (Org. Lett., 2005)

(untitled) - Lin, Y.; Liu, L.; Du, D.-M. (Org. Chem. Front., 2017)